Dutch Curse on Indonesia: Unemployment by Asian Development Bank (ADB) Loan Projects - Muhammad Amir Ingratubun; Ardika Perdana Fahly; Beny Cahyadie; Nefo Indra Nizara; Raden Ratih Rantini (Gadjah Mada International Journal of Business, 2021)
The ADB takes more than five years to disburse the agreed-upon loan funds after the borrower signs the loan agreements, because of the conditionalities attached to such loans, compared with it only taking one day for commercial banks to release any agreed loans. During this five-year period, the funds stay in the bank and gain compounded interest, disfavoring Indonesia. Development studies have mostly overlooked these gains and their impacts. Knowing that ADB loans cause about 3% of Indonesia’s unemployment, we reviewed the delay’s impacts during a project’s implementation on unemployment involving 325 ADB loan projects, valued at over $33 billion, from 1969 to 2017. We used a non-econometric methodology by adopting the management principles of the project and portfolio. The results show that the ADB’s loans at 1% GDP initially helped Indonesia reduce its unemployment by 30%. However, because of the ADB’s standard implementation of five years, along with an extra two-year delay (seven years in total) we observed shorter unemployment reductions by half, but then reversed, increased and tripled joblessness. This is also causing Indonesia to suffer capital losses of $0.6 to $12 per $1 of loan money, which is equivalent to 4.98% of its GDP because of the delays in the disbursement of the funds. ADB loans have severe negative effects, with over 200% volatility because of the delays. Fixing this is simple but requires a paradigm shift.